ЕНЕРГЕТИЧНИЙ БАЛАНС І ЧИСТА ЕФЕКТИВНІСТЬ РОСТУ ПЛОСКОЇ УСТРИЦІ (OSTREA EDULIS L.) - Ситник, Н. О.; Золотницький, О. П. (Marine Ecological Journal, 2023)
Energy balance and pure efficiency of growth (coefficient of K2) of flat oyster (Ostrea edulis L.) in ontogenesis is investigated. General tendencies of changes of its separate components and distribution of power spending on individual production, power exchange, assimilated and consumed food in the process of growth are found out. Description of seasonal variations of pure efficiency of growth, related to of temperature of water and body mass, dynamics of which are described by equation of multiple regression, is given. It is shown that maximal value of K2 0.63 - 0.67 makes for the invested species.